2020
DOI: 10.1016/j.tcs.2019.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Minsum k-sink problem on path networks

Abstract: We consider the problem of locating a set of k sinks on a path network with general edge capacities that minimizes the sum of the evacuation times of all evacuees. We first present an O(kn log 4 n) time algorithm when the edge capacities are non-uniform, where n is the number of vertices. We then present an O(kn log 3 n) time algorithm when the edge capacities are uniform. We also present an O(n log n) time algorithm for the special case where k = 1 and the edge capacities are non-uniform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 23 publications
(46 reference statements)
0
22
0
Order By: Relevance
“…Formulae (6) and (7) were first shown by Kamiyama et al [38] while (8) and (9) were shown in [33,35]. Note that i L (x) (resp.…”
Section: K-facility Location In Pathsmentioning
confidence: 93%
See 4 more Smart Citations
“…Formulae (6) and (7) were first shown by Kamiyama et al [38] while (8) and (9) were shown in [33,35]. Note that i L (x) (resp.…”
Section: K-facility Location In Pathsmentioning
confidence: 93%
“…On the other hand, the minisum facility location problems in dynamic flow networks have not been studied much except for the problem in path networks [6,7,33,35]. Paper [33] treated the minisum k-facility location problem in a dynamic flow path network with uniform edge capacity, and proposed an O(kn 2 ) time algorithm, which was improved to min{O(n 2 √ k log n + n 2 log n), n 2 2 O( √ log k log log n) } by the same authors in [35].…”
Section: Optimal Facility Location Problems In Dynamic Networkmentioning
confidence: 99%
See 3 more Smart Citations